Establishing A Guideline and Decision-Making Approach For UAE Solar Assets Waste Management By Utilising PVsyst - AL-ALI, AMEL (2023)
As the number of solar panel installations increases, the amount of discarded panels is also expected to escalate to an estimated 60 million tons by 2050, assuming a lifespan of 20-30 years for the panels. It is a newly declared global concern for the need to manage this new technology waste. End-of-life solar panels contain valuable components, but there currently needs to be globally documented guidelines in place to manage this type of waste efficiently. This paper studies solar PV waste in relation to EOL end-of-life management of PV assets installed in a solar park in the United Arab Emirates. Given the specific research limitations in implementing the proposed methodologies, the researcher conducted a comparative analysis by studying four different climatic regions: the UAE, Canada, India, and Norway, to bridge the gap and reinforce the validity of the results. The lack of comprehensive global guidelines and frameworks that guide decision-making regarding photovoltaic (PV) panel waste disposal and insufficient research on managing such waste are the driving forces behind this study. The study aims to address this gap by identifying the factors that affect the performance and efficiency of photovoltaic energy systems, specifically in the United Arab Emirates, a country known for its extremely hot and dry climate, and to develop assessment approaches and guidelines. PVsyst simulation software has been used for system performance analysis and to support decision-making by examining specially designed technical flow charts. The PV panels' basic performance-related parameters and meteorological information were identified as essential elements for evaluating the overall performance. The study also identified the primary tools for making end-of-life (EOL) decisions. The results revealed that the photovoltaic system in the UAE solar park completed its end-of-life with a PR ratio of 80% sooner than expected, with 22 years compared to the 25 years predicted by the manufacturer. This leads to the conclusion that installing PV panels in hot climate regions accelerates the deterioration of PV panels. India, a country with very hot and rainy weather, also backed up these assumptions by reaching an 80.8% PR in 22 years. The study provides a clear understanding of the factors that must be considered when deciding where to install solar panels due to their impact on the efficiency and health of the panels, and the conditions that cause PV systems to fail earlier than expected, thus introducing more waste to the environment.